Changes in the quality of cancer care as assessed through performance indicators during the first wave of the COVID-19 pandemic in 2020: a scoping review - Ana Sofia Carvalho; Óscar Brito Fernandes; Mats de Lange; Hester Lingsma; Niek Klazinga; Dionne Kringos (BMC, 2022)
Abstract Background Cancer comprises a high burden on health systems. Performance indicators monitoring cancer outcomes are routinely used in OECD countries. However, the development of process and cancer-pathway based information is essential to guide health care delivery, allowing for better monitoring of changes in the quality of care provided. Assessing the changes in the quality of cancer care during the COVID-19 pandemic requires a structured approach considering the high volume of publications. This study aims to summarize performance indicators used in the literature to evaluate the impact of the COVID-19 pandemic on cancer care (January-June 2020) in OECD countries and to assess changes in the quality of care as reported via selected indicators. Methods Search conducted in MEDLINE and Embase databases. Performance indicators and their trends were collated according to the cancer care pathway. Results This study included 135 articles, from which 1013 indicators were retrieved. Indicators assessing the diagnostic process showed a decreasing trend: from 33 indicators reporting on screening, 30 (91%) signalled a decrease during the pandemic (n = 30 indicators, 91%). A reduction was also observed in the number of diagnostic procedures (n = 64, 58%) and diagnoses (n = 130, 89%). The proportion of diagnoses in the emergency setting and waiting times showed increasing trends (n = 8, 89% and n = 14, 56%, respectively). A decreasing trend in the proportion of earliest stage cancers was reported by 63% of indicators (n = 9), and 70% (n = 43) of indicators showed an increasing trend in the proportion of advanced-stage cancers. Indicators reflecting the treatment process signalled a reduction in the number of procedures: 79%(n = 82) of indicators concerning surgeries, 72%(n = 41) of indicators assessing radiotherapy, and 93%(n = 40) of indicators related to systemic therapies. Modifications in cancer treatment were frequently reported: 64%(n = 195) of indicators revealed changes in treatment. Conclusions This study provides a summary of performance indicators used in the literature to assess the cancer care pathway from January 2020 to June 2020 in OECD countries, and the changes in the quality of care signalled by these indicators. The trends reported inform on potential bottlenecks of the cancer care pathway. Monitoring this information closely could contribute to identifying moments for intervention during crises.